Energy Efficient Homes: Incentive Programs for Energy Efficiency - Nicholas W. Taylor; M. Jennison Kipp; Kathleen C. Ruppert (EDIS, 2008)
FCS-3268, a 4-page fact sheet by Nicholas W. Taylor, M. Jennison Kipp, and Kathleen C. Ruppert, is part of the Energy Efficient Homes series. It defines key terms, tells who offers energy incentives, what types of incentives there are, and what considerations homeowners should have. Includes references. Published by the UF Department of Family, Youth and Community Sciences, June 2008.